Aquinas's way to God: the proof in De ente et essentia - Kerr, Gavin (Oxford University Press, 2015)
Essence/esse distinction and composition -- The argumentation for real distinction in De ente, cap. 4 -- Essence -- Esse -- The proof of God -- The causal principle -- The Per aliud principle and infinite regress -- Esse tantum -- Creation